Boosting taxes for boasting about houses? Status concerns in the housing market - Johannes Schünemann; Timo Trimborn (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
There is empirical evidence that households use residential houses as status goods. In particular, people are shown to compare their houses with those at the top of the distribution. In this paper, we introduce a residential housing sector and status concerns for housing into a neoclassical model with heterogeneous agents. We find that status concerns exert a negative externality and calculate a progressive Pigovian tax schedule that corrects for the externality, implying a housing tax for rich households of 4.6%. Implementing the tax schedule is associated with a sizable welfare gain. We also find that when the utilitarian social planner is constrained to housing taxes, Pigovian taxation is not constrained efficient. Further increasing the tax for rich households to 7.9% would maximize welfare in the constrained optimum.
Keywords: E03; O10; D10; H21; R31; 330; Status Concerns; Residential Housing; Pigovian Tax; Constrained Efficiency